The Functional Properties of Lactobacillus casei HY2782 Are Affected by the Fermentation Time - Seung Hee Jung; Dong Ki Hong; So-Jung Bang; Keon Heo; Jae-Jung Sim; Jung-Lyoul Lee (Applied Sciences, 2021)
Maintaining probiotic effectiveness represents the most important task for the development of functional foods. Gastrointestinal stability and intestinal adhesion properties comprise one criterion for probiotic selection. Here, we investigated the benefits of milk fermented with Lactobacillus casei HY2782 at different fermentation times. The probiotic strain used was L. casei HY2782 and the reference strain was L. casei ATCC393 for comparisons. The samples were fermented for 7 days at 30 °C. We determined the pH, CFU/mL, survival rate during simulated gastrointestinal digestion, adhesion ability to HT-29 cells, and gene expression of tight-junction proteins known to regulate intestinal permeability in Caco-2 cells. L. casei HY2782 exhibited significantly higher survival rates in simulated gastrointestinal digestion during long-term fermentation than L. casei ATCC393. The adhesion ability to HT-29 cells was significantly increased with L. casei HY2782 (3.3% to 8.7%) after 7 days of fermentation; however, only a slight increase was observed for L. casei ATCC393 (3.1% to 4.7%). In addition, L. casei HY2782 can significantly increase the expression of genes encoding tight-junction proteins during long-term fermentation of milk. In conclusion, we confirmed that long-term fermentation could be a novel manufacturing process for fermented milk containing L. casei HY2782 and showed the beneficial effects.